Metaphase chromosome spread preparation of citrus species - Hoang Thi Nhu, Phuong; Truong Thi Nha, Uyen; Tran Thi, Nhung; Hoang Thanh, Tung (Academia Journal of Biology, 2025)
Citrus is one of the popular fruit crops in Vietnam with many commercial varieties, however, its cytogenetic characteristics are currently limited. This study was conducted to find out a procedure for metaphase chromosome preparation in some citrus species. The results showed that after a 4-hour treatment with 0.002 M 8-hydroxyquinoline solution, the mitose indices of the root tip samples differed by species. Specifically, the tangerine and orange samples yielded the highest results at 11:00 am, the lemon root sample at 10:00 am, and the kumquat sample at noon. The explants were fixed in carnoy solution for at least 24 h; in what, the cell wall could be digested with 5 M HCl in 7−10 min (orange) or 10−15 min (tangerine) or with 2% pectinase and cellulase mixture in 30−35 min for kumquat and lemon. Then, their stained in aceto-orcein for 7−10 min and observed under the microscope. As with previous research, the chromosomal set of the assessed samples revealed that they all possessed a chromosome set of 2n = 18. The study’s findings identified the factors influencing the quality and chromosomal dispersion of several citrus samples, as well as the sample fixing time. Therefore, this procedure for preparing specimens can be applied to other citrus-family plants for further cytoogenetics research.